2014
DOI: 10.7554/elife.04854
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cue reliability drives frequency tuning in the barn Owl's midbrain

Abstract: The robust representation of the environment from unreliable sensory cues is vital for the efficient function of the brain. However, how the neural processing captures the most reliable cues is unknown. The interaural time difference (ITD) is the primary cue to localize sound in horizontal space. ITD is encoded in the firing rate of neurons that detect interaural phase difference (IPD). Due to the filtering effect of the head, IPD for a given location varies depending on the environmental context. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 58 publications
9
73
1
Order By: Relevance
“…This is in agreement with previous data on low-frequency responses in the barn owl's core of the inferior colliculus [Wagner et al, 2007]. However, an inhomogeneous representation of the ITD has been observed downstream [Cazettes et al, 2014]. A homogeneous distribution is consistent with a Jeffress type representation of the ITD, based on timedelayed inputs.…”
Section: Evidence For Different Types Of Input Delayssupporting
confidence: 82%
See 1 more Smart Citation
“…This is in agreement with previous data on low-frequency responses in the barn owl's core of the inferior colliculus [Wagner et al, 2007]. However, an inhomogeneous representation of the ITD has been observed downstream [Cazettes et al, 2014]. A homogeneous distribution is consistent with a Jeffress type representation of the ITD, based on timedelayed inputs.…”
Section: Evidence For Different Types Of Input Delayssupporting
confidence: 82%
“…However, at frequencies below 3 kHz, this place code model is no longer the clearly optimal solution, and below 800 Hz a change to a population code model was predicted. Low-frequency data are scarce for the barn owl [Wagner et al, 2002[Wagner et al, , 2007Carr and Köppl, 2004;Cazettes et al, 2014]. The aim of the present study was to obtain in-vivo recordings from the low-frequency region of the NL to test predictions of optimal coding.…”
Section: Introductionmentioning
confidence: 99%
“…In these models, referred to as non-uniform population codes, the statistical structure of the environment is encoded in the non-uniform distribution of preferred stimuli and tuning curve shapes across the population. Studies in birds and humans are consistent with this theory (Fischer and Peña, 2011; Girshick et al, 2011; Cazettes et al, 2014). These studies have shown that the statistical relationship between environmental variables (such as image boundaries or the location of a sound source) and the sensory cues used to make inferences about these variables (edge orientation (Girshick et al, 2011) and interaural time difference (ITD) (Shi and Griffiths, 2009; Fischer and Peña, 2011), respectively) could be represented in the non-uniform tuning properties.…”
Section: Introductionmentioning
confidence: 55%
“…We calculated the environmental variability of IPD and ILD over different directions of concurrent noise sources (Cazettes et al, 2014). For each target direction, a white noise stimulus (0.5 – 12 kHz) was convolved with the head-related impulse responses for the left and right ears at the target direction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation